Simultaneous extraction and preconcentration of aniline, phenol, and naphthalene using magnetite–graphene oxide composites before gas chromatography determination. Issue 15 (8th July 2016) - Nazari, Najmeh; Masrournia, Mahboubeh; Es′haghi, Zarin; Bozorgmehr, MohammadReza
Abstract : The coextraction of acidic and basic compounds from different mediums is a significant concept in sample preparation. In this work, simultaneous extraction of acidic, basic, and neutral analytes in a single step was carried out for the first time. This procedure employed the dispersive solid‐phase microextraction of analytes with magnetic graphene oxide (graphene oxide/Fe3 O4 ) sorbent followed by gas chromatography with flame ionization detection. After the adsorption of analytes by vortexing and decantation of the supernatant with a magnet, the sorbent was eluted with acetonitrile/methanol (2:1) mixture. The parameters affecting the extraction efficiency were optimized and obtained as follows: sorbent amount 60 mg, desorption time 1 min, extraction time 5 min, pH of the sample 7, sample volume 20 mL, and elution solvent volume 0.3 mL. Under the optimum conditions, linear dynamic ranges were achieved in the range of 0.5–4, 0.25–4, and 0.25–2 μg/mL and limits of detection were 0.341, 0.110, and 0.167 μg/mL for aniline, phenol, and naphthalene, respectively. The relative standard deviations were in the range of 3.3–5.7% in eight repeated extractions. Finally, the applicability of the method was evaluated by the extraction and determination of analytes in stream water and drinking water samples and satisfactory results were obtained.